ENHANCING ANTIFUNGAL PROPERTY AND CYTOTOXICITY PROFILE OF GOLD NANOPARTICLES BIOSYNTHESIS VIA SOME FILAMENTOUS FUNGI WITH IN SILICO STUDY - Majeed, Suaded; Iman A. J. Al-Timimi; Abdullah H. Al-Saadoon (PT. Antis International Publisher, 2025)
Objective: To synthesize gold nanoparticles by fungi and testing their susceptibility as antifungals and comparing them with computerized study. Method: Synthesis of gold nanoparticles by some filamentous fungi (Aspergillus, Penicillium and Trichoderma), Au NPs characterised using (Transmission electron microscopy (TEM), Uv-vis spectrophotometer, Fourier transform infrared spectroscopy (FTIR), Energy-dispersive X-ray spectroscopy analyses (EDX), testing them as antifungals against pathogenic fungi (Candida albicans, C. tropicalis, Aspergillus niger, and A. flavus) and compared their results with nystatin as standard antifungal, the study was drawing a with In Silico study. Results: Aspergillus growth rate was more susceptible to nanoparticles, the percentage of growth rate was less than 70% after 48h, while Candida species were not affected by nanoparticles whether Au, and the percentage of growth rate was over 95%. The formation Au NPs confirm using UV-Vis with surface plasmon resonance at 540 nm and TEM images confirm spherical shape with average size 30 nm. The obtained data have been reported that therapeutic doses of nystatin that ranged from 8-1 μg/mL were not toxic significantly, and Au at 25% was not toxic effect significantly on cells growth. In silico study the results showed a characteristic binding affinity and conformational stability of Au-protein combination. Novelty: Synthesis of gold nanoparticles using filamentous fungi is best method and nanoparticles have a moderate antifungal activity compared to standard antifungal drug (nystatin).